Egg Consumption and Carotid Atherosclerosis in the Northern Manhattan Study - Goldberg, Sharon (2014)
BACKGROUND: The evidence supporting recommendations to limit intake of cholesterol rich foods is inconclusive. We aimed to examine the association between egg consumption and carotid atherosclerosis phenotypes, and the association with clinical vascular events in a prospective, urban, multi-ethnic population. METHODS AND RESULTS: The Northern Manhattan Study is a population based cohort to determine stroke incidence, risk factors and prognosis. A sub-cohort of 1,429 NOMAS participants with both carotid ultrasounds and comprehensive dietary information was evaluated (mean±SD age of participants 65.80±8.80, 40% male, 18% white, 20% black, 60% Hispanic). The association between egg consumption and carotid intima media thickness (cIMT) was assessed with linear regression. Logistic and quantile regression was used to examine the association between egg consumption and carotid plaque presence, thickness, and area. The relation between egg consumption and clinical vascular events (N=2669) was examined with Cox models. The mean total cIMT was 0.91±0.08 mm and 58% had carotid plaque present. Increasing egg consumption was inversely associated with cIMT, plaque presence, thickness, and area, in models adjusted for demographics, vascular risk factors and diet. For every additional egg consumed per week, the risk of plaque decreased by 11% (95% CI 3%-18%). No association was detected between egg consumption and risk of clinical vascular outcomes, over a mean follow up of 11 years and after adjustment for covariates. CONCLUSIONS: Frequency of egg consumption in the low to moderate range was inversely related to several markers of carotid atherosclerosis. No association with clinical vascular events, including stroke, was detected. Our findings do not support current vascular health guidelines suggesting the extreme limitation or avoidance of egg consumption due to its cholesterol content.